Mengembangkan Potensi Pariwisata Lombok Melalui Pelatihan dan Pemberdayaan Masyarakat Lokal - Risky Angga Pramuja; I Wayan Bratayasa; Putrawan Habibi (Pusat Kajian Pariwisata dan Publikasi Jurnal Sekolah Tinggi Pariwisata Mataram, 2023)
This research aims to develop tourism potential in Lombok through training and empowering local communities. The research was conducted by collecting data through surveys and interviews with local communities, as well as involving tourism-related stakeholders. The results of the study show that local people have a positive perception of the tourism industry, but their participation is still limited. Through skills training, local people can acquire the necessary knowledge and skills to be actively involved in the tourism industry. Training and empowering local communities have had positive impacts, including increased income, improved quality of products and services, and greater participation in owning and managing tourism businesses. However, there are still challenges that need to be overcome, such as cooperation between the government, tourism managers and local communities, access to training and resources, and sustainable tourism development. Recommendations for this research include expanding training programs, developing policies that support local community participation, and synergies between the government, the tourism sector, and local communities. This research is expected to provide guidance and a positive contribution in developing tourism potential in Lombok and other areas with a similar context